Efektivitas Metode Sing and Acting pada Penguasaan Mufrodat Bahasa Arab di Qur’anic School of Dewan Dakwah Surakarta - Al Azhary, Nabila (Jurnal Pendidikan Madrasah, 2026)
Vocabulary mastery is one of the essential elements in Arabic language learning because it serves as the foundation for language skills such as listening, speaking, reading, and writing. However, Arabic learning at the elementary level is still often carried out using conventional methods that make students easily bored and less active in the learning process. This study aimed to determine the effectiveness of the Sing and Acting method in improving Arabic vocabulary mastery among fifth-grade students of Qur’anic School of Dewan Dakwah Surakarta. This research employed a quantitative approach with a comparative ex post facto design. The subjects of this study were 29 students of class VB. Data were collected through tests, questionnaires, and observations. Data analysis was conducted using descriptive statistics and the paired sample t-test. The results showed that the average pre-test score of 76.86 increased to 87.68 in the post-test, with an improvement difference of 10.82. The hypothesis testing result showed a significance value of 0.000 < 0.05, indicating a significant difference between students’ learning outcomes before and after the implementation of the Sing and Acting method. Observation and questionnaire results also revealed that students became more active, enthusiastic, and easier to memorize vocabulary during the learning process. Therefore, the Sing and Acting method is effective in improving Arabic vocabulary mastery among elementary school students through active, enjoyable, and interactive learning.